Parenting systems and models in islamic boarding schools within the framework of islamic education - Nasrin, Hilalludin; Januardi, Haris; Shamsul Aiman Mua'mar bin Shamsul Bahrin (Yayasan Azhar Amanaa Yogyakarta, 2025)
Islamic boarding schools (pondok pesantren) are traditional educational institutions that play a significant role in shaping the character of students through in-depth Islamic education. The childcare system in pondok pesantren encompasses three main patterns: authoritarian, permissive, and democratic. Authoritarian childcare emphasizes strict discipline and full authority of caregivers, while permissive patterns grant more freedom to students, and democratic patterns strike a balance between authority and freedom. This research employs a literature review method to gather data from various relevant literary sources. The concept of childcare in pondok pesantren involves training, habituation, and awareness to cultivate students' religious personality and noble character. The principles of childcare in pondok pesantren include exemplary behavior, affection, discipline, mental and spiritual guidance, potential development, self-reliance, togetherness, obedience to parents and teachers, community service, and love for the homeland. Childcare models in pondok pesantren vary from authoritarian, democratic, to permissive, each with its own characteristics and impact on student development. Supporting factors for childcare in pondok pesantren include parental interest and trust, strict rules, character-based curriculum, and caregivers' enthusiasm in educating. Conversely, inhibiting factors include parental coercion and interference with pesantren rules. Efforts to overcome these obstacles involve parental understanding, rule socialization, caregiver capacity building, and cooperation among caregivers. Islamic childcare principles emphasize religious values, while national childcare principles focus on conditioning a safe, comfortable, and engaging environment for children.